KAPASITAS PENGANGGARAN DESA DI KABUPATEN MUNA PROPINSI SULAWESI TENGGARA - Jopang Jopang; Zulfiah Larisu; Arifin Utha; Eko Harianto (Universitas Halu Oleo, 2019)
The purpose of this study was to analyze and describe the capacity of village budgeting in Muna District. The approach used is qualitative research. The study was conducted in real-world settings, namely conducting in-depth investigations into the natural context in which the processes and outputs of village budgeting take place. The study locations are 7 seaside villages and 8 non-seas villages in Muna Regency. The scope of time is three budget years, namely 2015-2017. The main data collection procedure is the study of documents. To obtain primary data, procedures for public consultation and/or focus group discussion are taken. The technical public consultation was mutually agreed upon by involving the Community Empowerment Agency and Village Government of Muna Regency as the technical agency. Public consultation material was explored and developed from the results of focus group discussions. Focus group discussions were conducted at the village level, involving Village Devices, members of the Village Consultative Body, and Village Community Empowerment Institutions. Available data are analyzed by the procedure of content analysis and qualitative descriptive analysis to reveal the stages of the village budgeting process, who is involved and what is the main role.The results of the study show that the capacity of village budgeting in Muna Regency is not optimal, that is, the village budgeting system has not functioned properly in allocating and using inputs to produce budgetary outputs that are beneficial for achieving village development goals. Villages in Muna Regency have budget documents namely APB Desa and RAB which are stipulated by village regulations. Keywords: Capacity, Budgeting. Village